Tratamento clínico e evolução de crianças com cardiomiopatia dilatada acompanhadas em um serviço público de cardiologia pediátrica de referência - Jácome, Bruna Zanforlin (2022)
Introduction: Dilated phenotype cardiomyopathy (MCD) is the most frequent clinical presentation in childhood; its course can be progressive and has high cost of treatment. It is believed that the disease may have its prognosis improved with early diagnosis and treatment. Objective: To analyze aspects of the treatment, epidemiological profile, and evolution of children with DCM followed up in a public pediatric cardiology service of regional reference. Method: A descriptive and retrospective epidemiological study was conducted, based on a review of medical records of 40 patients with DCM treated between 2005 and 2020 at the Pediatric Cardiology outpatient clinic of the Clinical Hospital of the Federal University of Uberlândia (HC-UFU). Data were recorded regarding gender, age, weight, body height, clinical presentation of heart disease, functional class of heart failure and main echocardiographic parameters. The Kaplan-Meier estimator was applied to calculate the survival function empirically and the log-rank test in the survival analyses. Results: The mean age of the patients was 3.3 years; 65% were female. Most patients (65%) progressed to complete improvement of cardiac dysfunction with the clinical treatment instituted and 7.5% showed only partial improvement. The results obtained in the analyzed sample showed no difference related to gender regarding survival. The survival rate of children with DM before the second year of life was lower than those who had the diagnosis later. Conclusion: There was a predominance of females in the sample studied, with viral myocarditis being the most likely etiology. Most patients had HF in functional class IV at the time of diagnosis, with dyspnea being the main symptom. The probability of survival after one and five years of treatment was, respectively, 86.3% and 72.3%, with an overall mortality rate of 24.32%. There was no statistical difference between the sexes regarding the probability of survival and the survival rate before the second year of life was lower when the diagnosis occurred after this age. Lower LVEF indicators were lower prognosis in diagnosis and after treatment and the presence of cardiogenic shock. Full recovery occurred in 65% of patients after 14 months on average of clinical drug treatment that included ACI and their associations in more than 80% of cases. Children who had DCM before two years of age had worse clinical evolution.